INCREASING CHILDREN'S COGNITIVE ABILITY THROUGH NUMBERS BALL AT TK AISYIYAH BUSTANUL ATHFAL 3 TENGGARONG - Ananiah, Ananiah; Lestari, Lestari; Setiawan, Agus (Lembaga Penelitian dan Pengabdian kepada Masyarakat (Center for Research and Community Services), Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2019)
The background of this research is that children's cognitive abilities are lacking due to the lack of utilizing learning media, only using their fingers to say numbers. The teacher still focuses on using the singing method, so the children get bored and ignore the teacher. The purpose of this study was to improve the numeracy skills of children at Aisyiyah Kindergarten Bustanul Athfal 3 Tenggarong, Kutai Kartanegara Regency. Cognitive ability is an ability or thought process, namely the individual's ability to connect, assess, and consider an event or event. Indicators in this study include mentioning numbers 1-20, sorting numbers 1-20, connecting numbers with objects. This research is Classroom Action Research (CAR). The research was conducted in 2 cycles. 1 cycle consisting of 2 actions. Each cycle consists of planning, implementing, observing or observing, and reflecting. This research is collaborative between researchers and classroom teachers; data collection methods to improve cognitive abilities are collected through observation and documentation. Number ball game through indicators mentioning numbers 1-20, ordering numbers 1-20, and connecting numbers with objects. The results obtained from the two cycles were very significant in increasing children's cognitive abilities. Before the action was taken, the child's ability was still 32%, with the criteria for the child starting to develop (BB). After taking action, the child's development began to increase, namely, in the first cycle, the child's cognitive ability became 44% with the criteria for starting to develop (MB), in the second cycle, the child's cognitive ability increased to 73% with the criteria developing as expected (BSH). In cycle II, the agreed target was 70%. The conclusion of this researcher is that through playing numbers ball activities, children's cognitive abilities in TK Aisyiyah Bustanul Athfal 3 Tenggarong, Kutai Kartanegara Regency can be improved. Keywords: cognitive abilities, learning media, playing numbers ball activities